Investigation of price formation in different commodities in the seaborne trade : coal and iron ore - Lee, Bob Ren Wei (2016)
This paper focuses on investigating the factors that attribute to the price changes of the two most commonly traded dry bulk commodities – thermal coal and iron ore. For this research, I have separated the factors into three broad categories namely demand factors, supply factors and exogenous factors. Through qualitative analysis of historical data between years 2005- 2015 and interviews with relevant industry players, the main factor for the price formation of thermal coal and iron ore was identified. For thermal coal, demand factor was found to be the main driver for its price changes largely due to increased coal imports to China, apart from other demand factors like the construction costs of coal fired power plants and oil substitutes. On the other hand, supply and exogenous factors have a smaller influence to coal prices. The supply factors include the fluctuations in coal production from the output of existing or new coalmines, as well as the transportation costs of coal particularly sea freight rates. The exogenous factors identified include increased heating during winter seasons, constraints of coal transportation by sea, reduced coal production from heavy rains and carbon regulations like the ETS and USCAP. For iron ore, supply factor was found to be the main driver for its price changes owing to the oligopolistic supply model of the iron ore market. Apart from supply, the demand factor for iron ore involves China imports due to the country’s inherently low quality domestic iron ore. Other exogenous factors of iron ore price include the increase need for construction following large scale natural disasters, mining taxes imposed by the government that reduces supply and the transition of iron ore’s pricing mechanism from annual contracts to quarterly and spot prices, which in turn allows for a better reflection of iron ore price based on the market conditions. In addition to these findings, I have also provided a brief price forecast of coal and iron ore between 2017-2022 based on major foreseeable future events and their extent of influence to the change in commodity prices.